A novel electric-field-accelerated ion-sieve membrane system coupling potential-oscillation for alkali metal ions separation. (20th December 2017) - Du, Xiao; Ma, Xuli; Zhang, Pengle; Zheng, Junlan; Wang, Zhongde; Gao, Fengfeng; Hao, Xiaogang; Liu, Shibin; Guan, Guoqing
Abstract: A novel electric-field-accelerated ion-sieve membrane (EISM) system with potential-oscillation was set up for the selective separation of the alkali metal ions. The ion-sieve membrane was fabricated by coating a polypyrrole/polystyrenesulfonate composite on the stainless steel wire mesh (PPy/PSS/SSWM). In the EISM system, an external electric filed was applied by introducing a constant cell voltage on the two sides of the ion-sieve membrane to accelerate the directed transport of target ions through the membrane. Meanwhile, an extra pulse potential was applied on the PPy/PSS/SSWM membrane to adjust the ion binding ability of the PPy/PSS composite toward cations. As such, an enhanced "ion sieving effect" of the EISM system was achieved through the synergistic function of the constant cell voltage and potential oscillation, which resulted in the rapid transport of target cation across the membrane in a "leap-frogging" way. It is found that when an extra pulse potential of ±1.0 V (pulse width of 60 s) was applied on the EISM, the permeation flux of K + ions was increased by 7.42-fold with a constant cell voltage of 5 V. The permselectivities of the PPy/PSS/SSWM membrane for K + /Li + and K + /Cs + reached 3.29 and 3.45 respectively based on the optimized amplitude (±1.0 V) and frequency (pulse width of 60 s) of pulse potential. Graphical abstract: Highlights: An electric-field-accelerated ion-sieve membrane system was successfully developed. An extra pulse potential applied on the membrane accelerated the ion transportation. The ions transported across the membrane was realized in a "leap-frogging" way. Flux and permselectivity of K + were significantly enhanced in this system.